2018
DOI: 10.1093/treephys/tpx169
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phenology of dormant Japanese pear (Pyrus pyrifolia) flower buds: a possible cause of ‘flowering disorder’

Abstract: Mild winters influenced by global warming have increased the incidence of erratic flowering ('flowering disorder') in Japanese pear (Pyrus pyrifolia Nakai) trees in Japan. To discover how, when and what kind of disorder/damage occur in pear flower buds, we observed axillary flower buds of two cultivars, 'Kosui' (a mid-chill cultivar) and 'Niitaka' (a high-chill cultivar), grown at five locations. We focused on the phenology from autumn 2015 to spring 2016, when temperatures were higher than for average years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Although dormancy has been characterized by extreme changes in metabolic profile in fruit trees (Wang and Faust, 1990; Izadyar and Wang, 1999; Del Cueto et al , 2017; Ionescu et al , 2017), very little is known about the metabolic profile in pear, and specifically European pear dormancy. In this study, we focused on the major metabolite groups as described in other fruit species to create a correlation with chilling accumulation and dormancy break; among these were unsaturated fatty acids (Erez et al , 1997), sugars (Falavigna et al , 2018), and phospholipids (Izadyar and Wang, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although dormancy has been characterized by extreme changes in metabolic profile in fruit trees (Wang and Faust, 1990; Izadyar and Wang, 1999; Del Cueto et al , 2017; Ionescu et al , 2017), very little is known about the metabolic profile in pear, and specifically European pear dormancy. In this study, we focused on the major metabolite groups as described in other fruit species to create a correlation with chilling accumulation and dormancy break; among these were unsaturated fatty acids (Erez et al , 1997), sugars (Falavigna et al , 2018), and phospholipids (Izadyar and Wang, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Our expression analysis of PpMADS13-3 and PpFLC3-like collectively suggested that endodormancy and flowering progression may be different between NTs and FDTs, although further functional studies will be required to understand the physiologic function of PpFLC3-like. Ito et al (2018) reported that the instability of endodormancy causes flowering disorder. Based on changes in dormancy depth and gene expression in the present study, the depth of endodormancy in FDTs was considered to be shallower than that in NTs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…On another note, in open field-cultivated Japanese pear, flowering disorder occurred in various areas of Japan in 2009 (NARO, 2015 <https://www.naro.affrc.go.jp/org/niaes/ ccaff/project2015/manual2015/nihon-nashi_2015.pdf>). However, after that almost no flowering disorder occurred until it was identified again primarily in Kagoshima Prefecture in southern Japan in 2016 (Ito et al, 2018), which was primarily due to the instability of endodormancy induction affected by unseasonably high temperatures in autumn and winter (Ito et al, 2018), as well as the decreased freezing tolerance of dormant branches due to nitrogen application in autumn and winter (Sakamoto et al, 2017). Flowering disorder of greenhouse-cultivated trees may also be affected by unstable endodormancy because flowering disorder symptoms were similar between greenhouse-and open field-cultivated 'Kosui' (Tominaga et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Delays of dormancy breaks have been reported to date for Mediterranean and Japanese settings [14,15,48,49]. For Germany, rather stable dates of dormancy fulfilment for the past years and delayed or no fulfilments for future years were reported, with dormancy break dates between DOY −20 and 20 for apple cultivars with low chilling requirements (700 Chill hours) as well as a high inter annual variability [20].…”
Section: Shifts In Phenological Phasesmentioning
confidence: 99%